Traditional Sustainable Forest Management Practices among the Applai Kankana-ey Community of Bas-ang Tadian Mountain Province - Joshua P. Sammat; Reymark P Rivera; Jay Mark G. Cortado; Angelo L. Lozano (CV. Literasi Indonesia, 2025)
This research contributes to the documentation of the indigenous knowledge and social practice of the Kankana-ey in Bas-ang. This study determined the socio-demographic profile of the respondents and assessed their level of awareness and extent of knowledge on TSFMP, quantified the effectiveness of the adoption of TSFMP, and determined the significance of practicing the distinct TSFMP of Bas-ang. The data collected from a total of 234 respondents has been interpreted and analyzed using descriptive statistics. Results show that most respondents are aged 41-45, while those aged 71-75 are the lowest. In terms of gender, 60.17% are male. In civil status, 92.17% are married. In addition, many did not finish college degrees, and a few did not receive formal education. Given their educational background, some are construction workers. Painters, mechanical technicians, and OFWs were determined to be the lowest respondents. The challenges met by the respondents, however, were poor information dissemination on factors affecting TSFMP and knowledge in performing “id-idew” and marking of trees (gitabam).